Pengaruh Kecepatan Screw Conveyor dan Kecepatan Pisau Pemotong terhadap Massa Bakso pada Mesin Pencetak Bakso - Ardhi Prawira Rohim; Siti Duratun Nasiqiati Rosady (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This study aims to analyze the effect of variations in screw conveyor speed and cutting blade on an automatic meatball molding machine in producing meatballs weighing between 15 and 20 grams. The research method used a design of experiments (DOE) approach with a factorial design, followed by a two-way ANOVA analysis to test the effect of each factor and their interactions. The screw conveyor speed variations used were 160 RPM, 140 RPM, and 124 RPM, while the cutting blade speed was varied at 224 RPM, 186 RPM, and 160 RPM. The speed variations were obtained by adjusting the pulley ratio on the machine. The testing process was carried out by molding meatballs using a combination of these speed variations, then boiling them until they float to ensure doneness. After that, the mass of each meatball was weighed with a precision scale. The weighing data were processed using Microsoft Excel and Minitab 21 software to obtain accurate statistical analysis. The results showed that increasing the screw conveyor speed tended to increase the meatball mass, while increasing the cutting blade speed actually decreased the mass of the meatballs produced. The interaction between screw conveyor speed and cutting knife speed was statistically significant with a p-value ≤ 0.05, indicating that the combination of the two plays an important role in determining the final meatball mass. Through Response Optimization analysis, the most optimal combination for producing meatballs with a mass in the range of 15–20 grams is a screw conveyor speed of 124 RPM and a cutting knife speed of 160 RPM. This setting can be achieved by using pulleys with diameters of 114.3 mm (4.5 inches) and 88.9 mm (3.5 inches). These findings are expected to be a reference for meatball industry players, especially MSMEs, in increasing production efficiency and maintaining product size consistency.